Glial-mediated immune modulation in glaucomatous neurodegeneration: mechanisms and therapeutic implications - Zong, Fangwei; You, Jiaxin; Wu, Hong; Wang, Xuerui (Frontiers in Immunology, 2025)
Glaucoma, a leading cause of irreversible blindness, is characterized by retinal ganglion cell (RGC) degeneration and optic nerve damage. While elevated intraocular pressure (IOP) is a major risk factor, emerging evidence highlights neuroinflammation as a critical driver of disease progression. Glial cells, particularly microglia, astrocytes, and Müller cells, are central to this inflammatory process, orchestrating immune responses through the release of cytokines, chemokines, and complement proteins. Microglia and astrocytes contribute to early inflammatory amplification through tumor necrosis factor-alpha (TNF-α), complement, and Toll-like receptor 4 (TLR4) pathways, while Müller cells further promote tissue damage via ATP/P2X7R signaling and senescence-associated mechanisms. Leukocyte infiltration, triggered by glial-derived chemokines and matrix metalloproteinases (MMPs), underscores the intersection of innate and adaptive immunity in glaucoma. Importantly, preclinical studies demonstrate that targeting neuroinflammatory pathways confers RGC protection, thus modulating glial activation and immune signaling represents a promising therapeutic strategy for glaucoma, particularly in IOP-refractory cases. This review synthesizes current knowledge on the role of glial cells in initiating and perpetuating immune responses that exacerbate RGC loss, and details how activated microglia and astrocytes release pro-inflammatory mediators and upregulate pathogenic signaling pathways.